A current opinion on the antimicrobial importance of popular pepper essential oil and its application in food industry. Issue 1 (2nd January 2019) - Myszka, Kamila; Leja, Katarzyna; Majcher, Małgorzata
ABSTRACT: Food safety is a fundamental concern of consumers, regulatory agencies, and the food industry. Increasing the morbidity of foodborne diseases, coupled with economic implications, makes continual efforts for safer foods production and developing new antimicrobial agents necessary. The alternatives to chemical preservatives are natural ones that are nontoxic, such as pepper. Pepper essential oils can be used both as flavor improvement agents and as efficient preservatives of food products. The present review attempts to provide an overview of the most bioactive ingredients of pepper essential oils and to describe their mode of hypothetical antimicrobial action. We examined data from the literature to understand the complex mechanism of interaction between bioactive compounds of pepper and microbes. The novel application possibilities of pepper oils in food technology, especially in meat, fish, and vegetable processing, were also described.